Obesity difference on association blood malondialdehyde level and diastolic hypertension in the elderly population: a cross-sectional analysis - Ying Huang; Hong Chen; Qifan Liu; Jinzhu Hu; Dongxi Hu; Zixi Huang; Zhenyan Xu; Rong Wan (European Journal of Medical Research, 2023)
Abstract Aims Although increased production of malondialdehyde (MDA), an end product of lipid oxidation caused by reactive oxygen species (ROS), has been found be elevated in hypertensive population, whether MDA contributed to a changed risk of hypertension is uncertain. We aimed to investigate whether elevated blood levels of MDA contribute to increased risk of hypertension and obesity has a modified effect on the association in an older Chinese population. Methods Data were obtained from 2011 to 2012 of the Chinese Longitudinal Healthy Longevity Survey (CLHLS), a national cohort of older adults in China. Associations between blood MDA level and systolic and diastolic blood pressure (BP) and risk of hypertension were performed by multivariable linear regression and logistic regression analysis. Results The results of smooth curve revealed a gradual upward trend on association of blood MDA level with diastolic BP (P < 0.001), but not with systolic BP (P > 0.05). Logistic regression analysis suggested that elevated blood MDA levels were associated with increased risk of diastolic hypertension (OR = 1.079, 95% CI 1.039–1.122, P < 0.001) rather than systolic hypertension (OR = 0.978, 95% CI 0.943–1.015, P = 0.247) after adjustments of related confounding factors were made. Furthermore, we found the significant modification effect of obesity on the association between MDA level and risk of diastolic hypertension evaluated by body mass index (BMI, interaction P = 0.015) and by waist circumference (interaction P = 0.016). Conclusion Our results firstly identified that increased blood MDA levels were associated with elevated risk of diastolic hypertension, rather than systolic hypertension in the non-obese old population.